Post treatments effect on TiZr nanostructures fabricated via anodizing - Vardaki, Maria; Mohajernia, Shiva; Pantazi, Aida; Nica, Ionela Cristina; Enachescu, Marius; Mazare, Anca Valentina; Demetrescu, Ioana; Schmuki, Patrik (Journal of Materials Research and Technology, 2019)
The primary focus of the paper is the fabrication of nanotubes via a two steps anodizing procedure on a TiZr substrate followed subsequent annealing treatments and their effect on surface and biocompatibility. The two step anodizing process is optimized for obtaining uniform and ordered nanotubular structures, that are then annealed in air or reduced in an Ar/H2 environment. The high aspect ratio nanotubular structures (diameter 160 nm, length 9.4 μm) maintained their morphology after annealing or reduction. While the thermal treatments burned-off the fluoride, they converted the tubes to ZrTiO4 (annealing in air) or (Zr0.333 Ti0.666)O2 (reducing). Surface roughness and adhesion forces evaluation of the nanostructures was included in the AFM investigations, and show that these properties can be tuned. In vitro cell response to TiZr substrate and nanotubular coatings were analyzed using HGF-1 gingival fibroblasts cell line and LDH, nitric oxide (NO) and reactive oxygen species (ROS) tests. Regarding the hydrophilic balance of the studied samples, as expected it decreased after annealing and but increased after reduction, with only small change in the cell response. The results suggest that these coatings are biocompatible with human gingival fibroblast and can be used in biomedical applications without generating any considerable inflammatory process.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Adhesion; Anodizing; Biocompatibility; Roughness; Thermal treatments